(untitled) (Indian Journal of Child Health, 2019)
Introduction: The high incidence of low birth weight babies in India is due to the neglect of health and education of females, teenage marriages, frequent pregnancies, maternal malnutrition, ?nemi?, and infections. Objective: The objective of his study was to identify the role of various maternal factors such as maternal age, parity, regular antenatal care (ANC) visits, weight, anemia, socioeconomic status, and maternal pre-eclampsia affecting the nutrition of the fetus. Materials and Methods: In this observational study, 500 mother-infant pair recruited, consecutively. A detailed antenatal and postnatal history of the mother was recorded. Information obtained were age, the weight of mother, parity, number of antenatal visits, and maternal hemoglobin (Hb). Newborn taken for the study was weighed and assessed for their nutritional status using the clinical assessment of nutrition score. Results: Of 500 babies, 51.4% of babies were born to mothers aged ?20 years; and out of them, 76.5% of babies had fetal malnutrition. About 45.2% of babies born to primigravidae mother; of which, 85.9% had fetal malnutrition (FM). About 54.8% of babies born to multigravida mothers; of which, 45.3% had FM. Of 69.2% of mothers, who had irregular or no ANC, 75.1% of babies had FM. Mothers with weight ?50 kg were 45.6% and 78.9% of their babies had FM. In 44% of mothers, Hb was ?10 g% and 91.8% of babies born to these mothers had FM. Of 48.80% of babies born to pre-eclamptic babies, 77.5% of babies had FM. All these maternal factors were statistically significant in their impact on FM (p<0.05). Conclusion: Maternal nutrition and well-being are essential to bring down the percentage of FM in babies. Proper education not only of the mother but also of society as a whole, recognition of these factors and timely intervention will go a long way not only in improving the quality of life of babies born to such mothers but also in reducing the economic burden on a precariously balanced health-care system.